Evolution and sense of the school autonomy - Cuadrado Muñoz, Francisco J. (Avances en Supervisión Educativa, 2019)
School autonomy has had a long history in the successive laws of education in our context and it persists in time as unquestionable. It is necessary, therefore, to determine the evolution and the meaning of school autonomy that is currently being promoted in schools, the measures that are applied to their development, their effects, and the ultimate goal they pursue. Being a controversial issue that affects the functioning of different education systems in a globalized world, it is necessary to raise, and debate, especially when we need an education pact in this country, with a new education law, which allows us to resolve the difficult balance between efficiency and equity.